Normativas de prevención, seguridad laboral y ambiental de la corporación ecuatoriana de aluminio S.A. CEDAL. Propuesta de un sistema integral de OHSAS 18001 Y SART para su gestión y cumplimiento. - PlazaTapia, Gustavo Adolfo (2015)
‘La Corporación Ecuatoriana de Aluminio’ (CEDAL) S.A. was founded in 1974 as an extrusion company to meet the demand for architectural and structural aluminum profiles in the market. The plant was established in the city of Latacunga and started its production in 1976. International standards are currently handled, such as: ISO 9001 regarding quality management, ISO 14001 environmental management and OHSAS 18001 relating to the management of occupational safety and health, which is handled through the Department's integrated management system that is the entity in internal control issues: quality, industrial safety, occupational health and environment. The gradual growth of processes and expansion of the enterprise creates the need to comply with applicable local, national and international laws, To do this, a clear goal is arisen which is to design an integrated management system that links the three rules above and additional standards such as the system of audits of occupational risks known as SART. So, several information data, manuals, plans, procedures, formats and instructions have been implemented which will be easy to engage and relate for its company’s users and monitoring of the entity's internal control as external control entities by creating an integrated hybrid management system since a relationship between national and international standards approach is given. With this tool a great step is given to an effective management and ease integrated management system.